2010
DOI: 10.3109/17435390.2010.539712
|View full text |Cite
|
Sign up to set email alerts
|

Cd/Se/Te-based quantum dot 705 modulated redox homeostasis with hepatotoxicity in mice

Abstract: The objective of this study was to investigate whether quantum dot 705 (QD705) disrupts the cellular antioxidant systems leading to hepatotoxicity in mice. Mice were intravenously injected with QD705 and then sacrificed at week 12 or 16. Homeostasis of antioxidant-related metals, antioxidant activities, induction of oxidative stress, and toxicity in the liver were investigated. Although no histopathological change was observed, a time- and dose-dependent increase in metallothionein expression and reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 54 publications
7
42
1
Order By: Relevance
“…IL‐1β is one of the most potent proinflammatory cytokines that can induce rapid recruitment of neutrophils to sites of inflammation, activate endothelial adhesion molecules, induce cytokines and chemokines, and stimulate specific types of adaptive immunity (Sahoo, Ceballos‐Olvera, del Barrio, & Re, ). This results were consistent with other research (Lin et al, ). The inflammation response in the liver from QDs was closely related to the Kupffer cells, which are responsible for removing exogenous substances in the liver.…”
Section: Toxic Effects Of Quantum Dotssupporting
confidence: 94%
See 2 more Smart Citations
“…IL‐1β is one of the most potent proinflammatory cytokines that can induce rapid recruitment of neutrophils to sites of inflammation, activate endothelial adhesion molecules, induce cytokines and chemokines, and stimulate specific types of adaptive immunity (Sahoo, Ceballos‐Olvera, del Barrio, & Re, ). This results were consistent with other research (Lin et al, ). The inflammation response in the liver from QDs was closely related to the Kupffer cells, which are responsible for removing exogenous substances in the liver.…”
Section: Toxic Effects Of Quantum Dotssupporting
confidence: 94%
“…However, there are some studies that have shown that QDs have no significant effect on liver function or pathological damage, but can cause mild inflammation on liver tissue (Haque et al, ; Lin et al, ; Liu et al, ; Lu et al, ; Stanca et al, ). Lin et al studied ICR mice injected intravenously with CdTe/ZnS (40 and 160 pmol per mouse).…”
Section: Toxic Effects Of Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, HMOX1 protein expression may be a very promising general biomarker for TOPO-PMAT QD exposure in vivo. Indeed, Lin and co-workers (Lin et al 2010) have recently shown that intravenous injection of CdTe QDs into mice caused an up-regulation of HMOX1, as well as other biomarkers of oxidative stress and inflammation, in the livers of these animals. While other organs were not evaluated, this report confirms that HMOX1 is a promising candidate biomarker of exposure to QDs in general.…”
Section: Discussionmentioning
confidence: 99%
“…18 Liu et al 7 found that CdSe QDs caused significant impairment to the liver by oxidative stress, as characterized by a significant increase in reactive oxygen species and malondialdehyde (MDA) levels within hepatocytes. Park et al 19 have suggested that bioconjugation could reduce the level of oxidative stress and decrease the toxicity of CdTe QDs to mammalian cells.…”
mentioning
confidence: 99%